Management of visitor satisfaction by using mobile digital tools and services to create concept of smart destination - Gračan, Daniela (Array, 2021)
Tourism is a system that inevitably follows the technological advancement of other areas of social and economic life, especially in the domain of accessibility of all elements of tourist product offered by its basic unit - a tourist destination. Due to the inclination and the need to use mobile digital tools and services for visitors to better manage, the concept of the so-called "smart destination" is becoming increasingly important. However, as digital applications become increasingly saturated with everyday life and threaten the saturation of real and quality life, there is a need for selective access also in the domain of destination management through experience management and visitor satisfaction. Using the methodology of the survey questionnaire a survey has conducted on several tourist frequency locations in the destination, whose aim was to investigate the importance and participation of individual mobile applications in improving the visitor experience, among them the five most prominent. By applying correlation and regression analysis, results have been achieved, which applications most importantly participate in improving the visitor experience. The significance of this research is reflected in the design of a new tool for adaptive and selective introduction of new mobile applications in order to better target visitors in a destination and thus more effectively manage their experience.